Comparative Modelling and Experimental Verification of a PMSM Drive System - Boztas, Gullu (My University, 2022)
This paper presents a comparative study on three simulation models and an experimental model for a Permanent Magnet Synchronous Motor (PMSM) drive system. A realistic modelling and simulation of a PMSM drive system are very useful before developing an experimental study. In particular, analyzing the performance of the motor drive and control algorithm in a simulation environment provides many advantages. The motor and drive system can be tested by using a simulation environment with various realistic scenarios in order to reduce testing costs and time span. Therefore, a comparative simulation study was performed in this paper to show the simulation results similarity with real application results. Three PMSM drive systems were modelled by using MATLAB environment based on SimPowerSystems, Simscape Electrical, and based C-language. All models and experimental system were operated under the same conditions. These models were compared with each other and verified with an experimental system. The waveforms were analyzed comparatively such as current, speed, mechanical position of the motor.
Keywords: Simulation; Modelling; Permanent magnet synchronous motor; Experimental verification